ECOCRITICAL AND ECOTOURISM ANALYSIS OF EBIET SONGS - Ismawati, Esti; Anindita, Kun Andyan (Prosiding Konferensi Internasional Kesusasteraan, 2025)
This study examines the ecocritical dimension and the potential of ecotourism in the lyrics of Ebiet G. Ade, an Indonesian musician known for his sensitivity to humanitarian and environmental issues. Using an ecocritical approach, this study aims to explore how Ebiet’s songs represent the ecological crisis, the relationship between humans and nature, and spiritual reflections on natural disasters that occur in Indonesia. Furthermore, ecotourism values such as environmental conservation, local wisdom, and community education are also identified in the messages of his lyrics. Data were collected through lyric documentation and analyzed using a descriptive qualitative approach. Five songs, namely "Berjalan di Hutan Cemara", " Biarkanlah Hati yang Bicara", " Berita ke Kawan", " Untuk Kita Renungan", and " Camellia III" were analyzed using an ecocritical approach and the potential of ecotourism. It can be concluded that the five songs contain strong ecological narratives, both in the form of diction, metaphors, and social criticism of the exploitation of nature. The findings indicate that Ebiet G. Ade’s works function not only as works of art but also as a medium for environmental awareness campaigns and have the potential to support culture-based ecotourism. It can also be concluded that music can be an educational tool in building collective awareness of ecological issues and encouraging people to care more about environmental preservation and sustainable tourism.